Violence Against Women, Hate and Law: Perspectives from Contemporary Scotland - Barker, Kim (Palgrave Hate Studies, 2022)
1. The ‘Historical Curiosity’ of Violence Against Women in Scotland -- 2 – (D)Evolved Policy-Making: Women and Scotland -- 3 – Scotland’s History of Hate: From Public Order to Hate Crime and Back Again -- 4 – Gender and Hate: A Scottish Perspective -- 5 – Misogynistic Harassment -- 6 – Online Violence: A Blanket of Digital Sexism? -- 7 – Tackling VAW Through Scots Law: Alternative Proposals -- 8 – Conclusion: Towards Ending Violence Against Women.